Interpretasi Ayat-ayat tentang Jilbab: Studi Perbandingan terhadap Musṭafa al-Marāgî dan Hamka - Winona Lutfiah; Esya Heryana; Fitriani Fitriani; Raihan Raihan; Ruslan Sangaji (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the interpretation of the verses about the hijab, especially QS. al-Ahzab [33]: 59 and QS. an-Nūr [24]: 31 by comparing two interpretations, namely Musṭafa al-Marāgî in Tafsir al-Marāg and Hamka in Tafsir al-Azhar. The approach used is a qualitative approach through literature study by applying a descriptive analytical explanation system with a comparative interpretation method (muqāran). The results of this study indicate that there are differences in interpretation between Musṭafa al-Marāgî and Hamka regarding QS. al-Ahzab [33]: 59 and QS. an-Nūr [24]: 31, although both agree that the aurat is a part of the body that must be covered, however, they differ in giving the meaning of the veil, as well as in extending the veil. This research recommends to academics to develop it further. It is also expected to be additional information on the interpretations of scholars who are not contemporary, not as traditional and cultural, so that they are able to see a much more colorful variety of interpretations.